(3abg GddZI GdebGQf (B/s - (3GdSGeQGFj, GHQGgjes ((3HjQhJ (B:s (3OGQ GdYde ddedGjjf ,s, 1978)
(3jTed OQGSGJ aj abg GddZI jNJU HYVgG HGdYQHjI h jTed HYVgG ehVhYGJ ebGQfI aj GddZGJ GdSGejI GdGNQi(B- (3h gh eMGhdI QUjfI dYQV GJLGgGJ GdOGQSjf aj gPG GdehVhY h JUhjH cKjQ ef GdGQGA HYO fbOgG fbOG efgLjG(B- (3h aj gPG GdcJGH OQGSI bjeI aj JGQjN GdeTcdI GddZhjI h KfGFjI GdYQHjI h eG WQC Ydi LPhQgG ef RjGOI GhbdH Gh GeGdI cd gPG aj faj Ydej h GSdhH Hjf Wdj h ThGgO GdOQGSI ef GdbQGf GdcQje h GdTYQ GdLGgdj GdaUjM eY efGbTI dPdc h JHjGf GUhd GdCNP h aQhY GdJChjd(B- (3h aj GdcJGH ebGHdI aj GhLg GdUQa Hjf GdYQHjI h GdYHQjI h GdGQGejI ef MjK GdHfGA h GdGTJbGb h YhGed GdGYQGHs
Keywords: (3GddZI GdYQHjIs; (3GddZIs